2020
DOI: 10.2196/14890
|View full text |Cite
|
Sign up to set email alerts
|

Valuable Genomes: Taxonomy and Archetypes of Business Models in Direct-to-Consumer Genetic Testing

Abstract: Background Recent progress in genome data collection and analysis technologies has led to a surge of direct-to-consumer (DTC) genetic testing services. Owing to the clinical value and sensitivity of genomic data, as well as uncertainty and hearsay surrounding business practices of DTC genetic testing service providers, DTC genetic testing has faced significant criticism by researchers and practitioners. Research in this area has centered on ethical and legal implications of providing genetic tests … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 40 publications
(4 reference statements)
1
40
0
Order By: Relevance
“…To answer our research question, we employed a 3-step research approach that was informed by the studies of Remane et al [ 28 ] and Thiebes et al [ 29 ] and is shown in Figure 1 . As a first step, we set up a database of pertinent gamified mHealth apps from the Apple App Store and Google Play Store.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To answer our research question, we employed a 3-step research approach that was informed by the studies of Remane et al [ 28 ] and Thiebes et al [ 29 ] and is shown in Figure 1 . As a first step, we set up a database of pertinent gamified mHealth apps from the Apple App Store and Google Play Store.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, we draw on the taxonomy proposed by Schmidt-Kraepelin et al [ 20 ] as our classification scheme, because it (1) provides the opportunity of classifying holistic gamification approaches as it is not limited to single game elements, (2) has been explicitly built for health care apps, and (3) provides a concrete set of dimensions with mutually exclusive and collectively exhaustive characteristics. Further, the taxonomy has been derived based on the guidelines proposed by Nickerson et al [ 35 ], which combine inductive and deductive reasoning and have been extensively used to develop taxonomies for phenomena in health care [ 29 ]. Past research has shown that taxonomies developed based on the guidelines by Nickerson et al [ 35 ] are suitable classification schemes with regard to the development of archetypes through cluster analysis [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The deep and continuously increasing integration of digital technologies into our everyday lives, e. g. by mobile solutions, will revolutionize our view on health care. Quantifying one's health status will increasingly not solely be applicable within health care institutions but also to other organizations such as, for example, direct-to-consumer genetic testing providers [3]. It will rather become an ongoing task helping to predict, maintain or improve the quality of life, both for individuals and society.…”
mentioning
confidence: 99%